CHOP Deficiency Ameliorates ERK5 Inhibition-Mediated Exacerbation of Streptozotocin-Induced Hyperglycemia and Pancreatic β-Cell Apoptosis - Nam, Dae-Hwan; Han, Jung-Hwa; Lim, Jae Hyang; Park, Kwon Moo; Woo, Chang-Hoon (Molecules and cells, 2017)
Streptozotocin (STZ)-induced murine models of type 1 diabetes have been used to examine ER stress during pancreatic β-cell apoptosis, as this ER stress plays important roles in the pathogenesis and development of the disease. However, the mechanisms linking type 1 diabetes to the ER stress-modulating anti-diabetic signaling pathway remain to be addressed, though it was recently established that ERK5 (Extracellular-signal-regulated kinase 5) contributes to the pathogeneses of diabetic complications. This study was undertaken to explore the mechanism whereby ERK5 inhibition instigates pancreatic β-cell apoptosis via an ER stress-dependent signaling pathway. STZ-induced diabetic WT and CHOP deficient mice were i.p. injected every 2 days for 6 days under BIX02189 (a specific ERK5 inhibitor) treatment in order to evaluate the role of ERK5. Hyperglycemia was exacerbated by co-treating C57BL/6J mice with STZ and BIX02189 as compared with mice administered with STZ alone. In addition, immunoblotting data revealed that ERK5 inhibition activated the unfolded protein response pathway accompanying apoptotic events, such as, PARP-1 and caspase-3 cleavage. Interestingly, ERK5 inhibition-induced exacerbation of pancreatic β-cell apoptosis was inhibited in CHOP deficient mice. Moreover, transduction of adenovirus encoding an active mutant form of MEK5α, an upstream kinase of ERK5, inhibited STZ-induced unfolded protein responses and β-cell apoptosis. These results suggest that ERK5 protects against STZ-induced pancreatic β-cell apoptosis and hyperglycemia by interrupting the ER stress-mediated apoptotic pathway.